Keterampilan Pemecahan Masalah dan Pengambilan Keputusan Sebagai Keterampilan Pembelajaran dan Inovasi Peserta Didik Abad 21 - Ahmad, Hariadi; Furkan, Nuril (Yayasan Pendidikan Intan Cendekia, 2022)
Each individual has their own way of dealing with problems, these ways are influenced by learning and experience. Guidance and counseling services are based on efforts to assist developmental tasks, potential developments, and control the counselee's problems. Counselors are demanded to have a complete figure of counselor who includes academic and professional competence as a scientific basis in the implementation of guidance and counseling services. Problem solving and decision making skills are individual abilities in identifying problems, clarifying problems, knowing the causes and effects of problems, making decisions, presenting choices, daring to take and accepting risks. The steps in problem solving and decision making are: Awareness of the existence of a problem, identifying the causes of the problem, looking for alternative solutions, considering alternatives and making choices, implementing choices, and choices.